Efficacy of susceptibility-guided quadruple therapy with antibiotic resistance using the string test coupled with quantitative PCR for Helicobacter pylori eradication: a protocol of a multicentre, open, randomised clinical trial - Geliang Yang; Yi Cui; Shenke Zhang; Shuqin Hu; Sujuan Fei (BMJ Open)
Introduction Helicobacter pylori is a major health problem, with the high prevalence of H. pylori and the increasing antibiotic resistance rate in China. Antibiotic resistance is the main reason for the failure of H. pylori eradication. This study aims to evaluate the efficacy and safety of susceptibility-guided quadruple therapy with antibiotic resistance using the string test coupled with quantitative PCR (qPCR) for H. pylori eradication.Methods and analysis This is a multicentre, open, randomised clinical trial that will enroll 324 patients with H. pylori infection. Patients will be randomised to two groups for a 14-day treatment: Treatment group will be treated with proton pump inhibitor (PPI), bismuth with two different kinds of antibiotics susceptibly guided by string test coupled with qPCR, while control group will be treated empirically with PPI, bismuth with two different kinds of antibiotics. The types and dosages of bismuth, PPI and antibiotics administered in this trial are based on the 2022 Chinese Guidelines for the treatment of H. pylori infection and the Sixth Chinese National Consensus Report on the management of H. pylori infection. The primary endpoint is the eradication rate, while secondary endpoints include compliance, the incidence of adverse events and adverse drug reactions.Ethics and dissemination This study was approved by the ethics committee of the Third People’s Hospital of Zhengzhou (No. 2024-04-001-K02). The results will be published in the appropriate peer-reviewed journal.Trial registration number ChiCTR2400082768.